Ekonomie a štěstí - Pavel Štika (Charles University in Prague, Institute of Economic Studies (IES), 2008)
– In this paper I am trying to provide the reader with a brief overview of contemporary discussion about recently frequently mentioned topic of economics and happiness. In the last few years the number of publications related to happiness from the economic perspective growth exponentially. As the importance of this topic seems to grow significantly, I modestly intend to provide Czech public with a very starting reference point for further research in this field. In the first part I sum up the basic terms of subjective well-being and Easterlin paradox and give an overview of the most striking empirical observations. The second part shortly describes approach to the happiness problem of selected key historical personalities, namely Aristotle, Smith and Genovesi. In the third part I outline present key challenge for the economic theory - tackling with the reciprocity phenomenon.
Keywords: A11; B19; B59; D64; 330; happiness; Easterlin paradox; reciprocity; Anthonio Genovesi; history of economic thought; Zufriedenheit; Lebensqualität; Austauschtheorie (Soziologie); Wirtschaftswissenschaft; Dogmengeschichte